Diversity, astaxanthin production, and genomic analysis of Rhodotorula paludigena SP9-15 - Sukanya Phuengjayaem; Engkarat Kingkaew; Patcharaporn Hoondee; Pornchai Rojsitthisak; Boonchoo Sritularak; Worathat Thitikornpong; Somphob Thompho; Natapol Pornputtapong; Somboon Tanasupawat (Heliyon, 2023)
SP9-15 for further application.
Keywords: Antioxidant Activity and Oxidative Stress; Algal biology and biofuel production; Photosynthetic Processes and Mechanisms